Development of an urban greenhouse gas modelling system to support a London monitoring network. (7th September 2020) - Hoare, D; Jones, RL; Harris, NRP; Ferracci, V; Carruthers, D; Stidworthy, A; Forsyth, E; Rigby, M
Abstract : A greenhouse gas monitoring network is being developed across London that will allow independent evaluation of reported emissions based on atmospheric data. The first site is operational at the Thames Barrier, and in this work, two atmospheric dispersion models (NAME and ADMS‐URBAN) are compared to observed methane concentrations between 5 May 2018 and 31 July 2018. We find that the models simulate some of the major features in the data, with consistent data–model discrepancies suggesting errors in the emissions inventory.